Working Towards a Treat-to-Target Protocol in Juvenile Proliferative Lupus Nephritis – A Survey of Pediatric Rheumatologists and Nephrologists in Germany and Austria - Vollbach, Kristina; Schuetz, Catharina; Hedrich, Christian M.; Speth, Fabian; Mönkemöller, Kirsten; Brunner, Jürgen; Neudorf, Ulrich; Rietschel, Christoph; Hospach, Anton; Kallinich, Tilmann; Hinze, Claas; Wagner, Norbert; et al. (Frontiers in Pediatrics, 2022)
Background: To describe treatment practices for juvenile proliferative lupus nephritis (LN) class III and IV of pediatric rheumatologists and nephrologists in Germany and Austria in preparation for a treat-to-target treatment protocol in LN. Methods: Survey study by members of the Society for Pediatric and Adolescent Rheumatology (GKJR) and the German Society for Pediatric Nephrology (GPN) on diagnostics and (concomitant) therapy of LN. Results: Fifty-eight physicians completed the survey. Overall, there was a considerable heterogeneity regarding the suggested diagnostics and management of juvenile proliferative LN. Increased urinary protein excretion, either assessed by 24h urine collection or spot urine (protein-creatinine ratio), and reduced estimated glomerular filtration rate were specified as important parameters for indication of kidney biopsy to diagnose proliferative LN and monitoring of therapy. Corticosteroids were generally proposed for induction and maintenance therapy, most often in conjunction with either mycophenolate mofetil (MMF) or cyclophosphamide (CP) as steroid-sparing immunosuppressants. MMF was clearly preferred over CP for induction therapy of LN class III, whereas CP and MMF were equally proposed for LN class IV. MMF was most often recommended for maintenance therapy in conjunction with oral corticosteroids and continued for at least 3 years and 1 year, respectively after remission. Hydroxychloroquine was widely accepted as a concomitant measure followed by renin-angiotensin system inhibitors in cases of arterial hypertension and/or proteinuria. Conclusion: The majority of pediatric rheumatologists and nephrologists in Germany and Austria propose the use of corticosteroids, most often in combination with either MMF or CP, for treatment of proliferative LN in children. The considerable heterogeneity of responses supports the need for a treat-to-target protocol for juvenile proliferative LN between pediatric rheumatologists and nephrologists.